2018
DOI: 10.20524/aog.2018.0227
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep quality and mucosal healing in patients with inflammatory bowel disease in clinical remission

Abstract: BackgroundThe interaction between sleep and the immune system has been increasingly studied over the last decades. The aim of this study was to investigate the association between sleep quality and mucosal healing in patients with inflammatory bowel disease (IBD) currently in clinical remission.MethodsNinety patients with IBD in clinical remission were studied: 54 (60%) with Crohn’s disease and 36 (40%) with ulcerative colitis. All completed the Pittsburgh Sleep Quality Index, and mucosal healing was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
3
18
1
1
Order By: Relevance
“…This finding is in line with studies that show poorer sleep quality in women than in men [31,32]. Yet, it contradicts with a previous study, in which sleep quality was worse in female patients with UC compared to males with UC, and there was no significant gender difference between patients with CD [4]. This contradiction may be seen due to the differences in sample characteristics.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This finding is in line with studies that show poorer sleep quality in women than in men [31,32]. Yet, it contradicts with a previous study, in which sleep quality was worse in female patients with UC compared to males with UC, and there was no significant gender difference between patients with CD [4]. This contradiction may be seen due to the differences in sample characteristics.…”
Section: Discussionsupporting
confidence: 58%
“…Several chronic inflammatory and immune disorders, such as systemic lupus erythematosus and rheumatoid arthritis, can affect sleep quality [2,3]. This relationship was also seen between IBD and sleep quality [4]. Sleep disturbance may be seen in patients with IBD, but the reasons are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our subjective data builds on previous data showing that sleep disturbances exist in CD patients compared to controls and this difference is more pronounced with active CD patients. A survey study utilizing PSQI has shown a correlation of poor sleep to mucosal healing in small number of patients, despite clinical remission 28 . An additional study using electroencephalography showed more features of disturbed sleep in 8 pediatric patients with active IBD compared to 14 patients with IBD in remission and 24 healthy controls 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that good sleep can help reduce fatigue, improve quality of life and alleviate gastrointestinal symptoms in patients with IBD (9,10). In IBD patients, the relationship between sleep, and mucosal activity and recurrence has been confirmed (11,12). Therefore, it is very important to know the sleep status of patients, which will help provide the basis for further sleep intervention in the future, and help patients improve the treatment effect ultimately.…”
Section: Introductionmentioning
confidence: 97%